Shargel and Yu's applied biopharmaceutics and pharmacokinetics - Ducharme, Murray P.; Shargel, Leon, 1941- (McGraw Hill, 2022)
"The eighth edition represents the collective contribution of experts with intimate knowledge and experience in the selected subject areas. Each chapter was written to include practical applications of the theoretical material. Frequently asked questions are included to provide a discussion of overall concepts. Practice problems, clinical examples and learning questions are included in each chapter to show how these concepts relate to practical situations. This textbook remains unique in teaching basic concepts that may be applied to understanding complex issues that are essential for understanding drug development and safe and efficacious drug therapy. The primary audience is pharmacy students enrolled in pharmaceutical science courses in pharmacokinetics and biopharmaceutics. This text fulfills course work offered in separate or combined courses in these subjects. Secondary audiences for this textbook are research, technological and development scientists in pharmaceutics, biopharmaceutics, and pharmacokinetics"--